STRATEGI PENGEMBANGAN USAHA DEMPO PISANG SEBAGAI PRODUK KEUNGGULAN DAERAH - Astaginy, Niar; Sudarnice (Fakultas Ekonomi, Universitas Hasyim Asy'ari Tebuireng Jombang, 2019)
This research is a research that uses a descriptive qualitative approach with the aim to determine internal and external factors and analyze the strategy of developing banana dempo business as a superior product in the area of ​​Bombana Regency. This study uses a SWOT analysis with a matrix of IFE and EFE can be identified important factors from both the external environment and the internal environment that are the strengths, weaknesses, opportunities and threats of banana dempo business in Bombana district. Based on the problem formulation of the SWOT analysis in the IFE matrix shows that the strength and weakness factors have a total score of 2.54, this identifies that the banana dempo business in Bombana Regency is in a fairly strong internal position, where this business has internal strength both in terms of product and strategy. However, based on the EFE matrix shows that the opportunity and threat factor has a total score of 2.77 which means that the banana dempo business does not respond to the opportunities that exist and avoid threats in the industrial market. Developed in the Cartesian diagram that the banana dempo business in Bombana Regency is in quadrant III where the quadrant is a business that has a weak position. So it is expected to change the previous strategy because, the old strategy was feared difficult to be able to capture the opportunities that exist while improving the performance of the banana dempo business organization in Bombana Regency. The position in this quadrant is very dangerous if it does not change the strategy in the banana dempo business in Kolaka Regency, because from the results of the banana dempo business assessment must improve the quality of products and human resources by maintaining strength and must take advantage of opportunities that exist including government support and the use of technology in designing Banana dempo products in realizing superior population in Bombana district.